The Devil's half acre : the untold story of how one woman liberated the South's most notorious slave jail - Green, Kristen (Journalist) (Seal Press, 2022)
"While Confederate statues are brought down across the country, America is reckoning with its tumultuous past and the legacy of the darker chapters of our history. In The Devil's Half Acre, New York Times bestselling author Kristen Green draws on years of deep research to tell the extraordinary hidden story of young Mary Lumpkin, an enslaved woman who sought freedom and lit a path for liberation for thousands more. Enslaved and separated from her family when she was a child, Mary Lumpkin, born 1832, was later forced to secretly marry and have the children of the brutal slave-trader Robert Lumpkin. Together they lived on the premises of his notoriously cruel slave jail in Richmond, Virginia, known as the 'Devil's Half Acre.' In this destitute setting, Mary Lumpkin not only found a way to educate and free her children-and herself-but she managed to create something monumental. When Robert Lumpkin died and left his jail to Mary, she rented The Devil's Half Acre to a Baptist missionary and helped transform it into 'God's Half Acre,' a place where freed Black men could be educated. These same grounds where enslaved people were tortured and held before slave auctions eventually became the cornerstone for Virginia Union University, one of the nation's first HBCUs, which is still open today. Richly told and dramatically paced, The Devil's Half Acre reckons with America's heartbreaking past. Ultimately, Mary Lumpkin's story demonstrates that righting unspeakable wrongs can not only heal, but can empower generations to come"--